PRODUKSI FONOLOGIS PEMELAJAR BAHASA INGGRIS PEMULA TINGKAT SEKOLAH DASAR DI JAWA BARAT - Feisal Aziez; Shinta Aziez; Roveliana Rawi Pahu (Khazanah Pendidikan, 2022)
The current study aims at analysing phonological production of Sundanese beginner EFL learners in an elementary school in West Java. This study analyses both the production of vowels and consonants that are particularly present in English language but are not in the learners’ L1 i.e., Sundanese. Qualitative approach was used in the study. Participants were asked to read two English short stories titled “A Good Boy” and “A Greedy Mouse” while being recorded. Their recording was then transcribed using phonetic transcription. The learners’ phonological productions were then classified using the chart from the International Phonetic Alphabet (IPA). The study shows that the Sundanese EFL learners’ phonological production is heavily influenced by their first language.  There are several common mistakes found in the learners’ production of vowels, such as [a] ↔ [Ʌ], [e], [eə], [u:], [ɔ] 2. [ə] ↔ [e], [u], [Ʌ], [ei], [a], [aʊ], [ʊə] 3. [ʊ] ↔[u], [ɔ] 4. [i:] ↔ [I], [e], [ə] 5. [з]→[ei], [e], [ə] 6. [əʊ]→[ə], [ɔ], [ɔi], [u], [з] 7. [æ]→[e], [ei], [a], [ɔ], [i:], [Ʌ] 8. [aʊ]→[u], [a], [ɔ], [ə] 9. [ɒ]→[ə], [a], [ɔ], [e]. MIn the production of consonants, the common mistakes are: 1. [ð] ↔ [d], [h], [t], [ʤ], [ʧ] 2. [ʃ] ↔ [s], [ʧ] 3. [v], [f] →[p] 3. [ʤ]→[k], [ʧ], [g], [r] 4. [ŋ]→[n], [g], [s] 5. [k]→[ʧ], [ŋ] 6. [Ɵ]→[d], [t] 7. [d]→[h], [t], [n], [j], [l] 8. [ʧ]→[t], [ʃ] 9. [j]↔[r] 10. [l]↔[d] 10. [w]→[s], [j] 11. [n]↔[d] 12. [t]→[n], [h]. The results confirm several previous studies which consequently suggests that these learners need specific approach in EFL learning if their target is to be as close as possible to the standard pronunciation of English.